Detection of Leishmania braziliensis in human paraffin-embedded tissues from Tucumán, Argentina by polymerase chain reaction - Córdoba Lanús, Elizabeth (2005)
American cutaneous leishmaniasis (ACL) is an endemic disease in Northern Argentina. We applied the polymerase chain reaction (PCR) followed by a hybridization labelled probe to 21 paraffin embedded human skin biopsies, already analyzed histologically, from leishmaniasis endemic areas in the province of Tucumán, Argentina. We used primers previously designed to detect a Leishmania-specific 120-base-pair fragment of kinetoplast DNA minicircle, other two primer pairs that amplify kDNA minicircles belonging to the L. braziliensisand L. mexicana complexes respectively, and specific oligonucleotide primers to detect L. (V.) braziliensiswhich amplify the sequence of the ribosomal protein L-14 of this species. The PCR-hybridization showed a sensitivity of 90.5% when compared to the histopathology test which was 61.9%. Five of the total samples analyzed were positive for the L. braziliensis complex whilst none was positive for the L. mexicanacomplex. The specific primers for L. (V.) braziliensisdetected the parasite in four samples. These results are consistent with those reported for close endemic areas and demonstrate that the causative agent of human leishmaniasis in the analyzed cases was L. (V.) braziliensis. PCR should be used as a diagnostic tool for tegumentary leishmaniasis, especially in the mucosal form, and as a valuable technique for the identification of the Leishmania species that causes the disease in certain areas.